y-1=-2(-3--2)

Simple and best practice solution for y-1=-2(-3--2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-1=-2(-3--2) equation:


y-1=-2(-3--2)

We simplify the equation to the form, which is simple to understand
y-1=-2(-3+2)

Simplifying terms in parentheses
y-1=-2*(-1)

Reorder the terms in parentheses
y-1=+(+2)

Remove unnecessary parentheses
+y-1=+2

We move all terms containing y to the left and all other terms to the right.
+1y=+2+1

We simplify left and right side of the equation.
+1y=+3

We divide both sides of the equation by 1 to get y.
y=3

See similar equations:

| 7y-17=11 | | 4(x-7)+6=2(x-5) | | 2y+1*26= | | 6(x+1)=6x-1 | | X+195=316 | | N^4+6=16 | | 6x+33=14x-39 | | 9a^2+15a= | | 4x+3/4=5x-3/4 | | X+19=31 | | X+19=3# | | 2x-2=9x+5 | | 2x=-11 | | X+75=123 | | 100-7(2x+3)=20 | | 4x-7=x^2 | | .3=0.2(c-1) | | -6(2x-5)+4=-12+34 | | 7a+4a+6=73 | | 1.8(1.5+a)=7.2 | | 11c-88=-22-(-8c) | | 5w-35=65 | | -T+5=T-15 | | 3x+11+110=6x+4 | | 3(6+r)=33 | | 1x(x-7)=30 | | 2x^2+5x-8=-13 | | -6(2y+2)=12 | | 5x^2=-6x+1 | | 16t-15=11t-11 | | (x-2)=0.8(4-y) | | (-3)(5)(10)(-2)(5)= |

Equations solver categories